Influence of intercultural factors in the administrative management of collaborators in a Peruvian jungle municipality - Gaby Carrion Paz; Gilberto Carrion Barco; Percy Ismael Salcedo Rodas; Denny John Fuentes Adrianzen (Universidad Ciencia y Tecnología, 2022)
This research was developed with the purpose of determining the level of influence that exists between intercultural factors and administrative management in the provincial municipality of El Dorado, San Martin in the Peruvian jungle. It was based on an applied quantitative methodology with a correlational scope and non-experimental design. The sample consisted of 49 participants, the survey technique was used for data collection and two questionnaires were applied as instruments, one for the interculturality variable with 20 items and the other for the administrative management variable with 18 items, both with a Likert scale. The results indicated that the intercultural factors influence administrative management with a positive correlation from moderate to high, likewise the coefficient of determination, R2 has a value of 0.5288 which indicates that 52.9% of the intercultural factors contribute to the administrative management of the entity.Keywords: Interculturality, coexistence, participation, administrative management.